Genome-Wide Investigation of SBT Family Genes in Pineapple and Functional Analysis of AcoSBT1.12 in Floral Transition - Jin, Xingyue; Liu, Yanhui; Hou, Zhimin; Zhang, Yunfei; Fang, Yunying; Huang, Youmei; Cai, Hanyang; Qin, Yuan; Cheng, Yan (Frontiers in Genetics, 2021)
SBT (Subtilisin-like serine protease), a clan of serine proteolytic enzymes, plays a versatile role in plant growth and defense. Although SBT family genes have been obtained from studies of dicots such as Arabidopsis thaliana, little is known about the potential functions of SBT in the monocots. In this study, 54 pineapple SBT genes (AcoSBTs) were divided into six subfamilies and then identified to be experienced strong purifying selective pressure and distributed on 25 chromosomes unevenly. Cis-acting element analysis indicated that almost all AcoSBTs promoters contain light-responsive elements. Further, the expression pattern via RNA-seq data showed that different AcoSBTs were preferentially expressed in different aboveground tissues. Transient expression in tobacco showed that AcoSBT1.12 was located in the plasma membrane. Moreover, ectopic overexpression of AcoSBT1.12 in Arabidopsis exhibited delayed flowering time. In addition, under the guidance of bioinformatic prediction, we found that AcoSBT1.12 could interact with AcoCWF19L, AcoPUF2, AcoCwfJL, Aco012905, and AcoSZF1 by yeast-two hybrid (Y2H). In summary, this study provided valuable information on pineapple SBT genes and illuminated the biological function of AcoSBT1.12 in floral transition.